نکاح کی کم از کم عمر: قرآن ، فقہِ اسلامی اور معاصر قانون کا مطالعہ: Minimum Age of Marriage: A Study of the Quran, Islamic Jurisprudence, and Contemporary Law (Al-Qamar, 2025)
This study explores the question of the minimum marriageable age through the lens of the Qur’an, Islamic jurisprudence, and contemporary legal frameworks. It demonstrates that the Qur’an neither prescribes nor legitimizes underage marriages; rather, such interpretations stem from cultural practices, selective readings of verses, and a misapprehension of the reports concerning Hazrat Aisha’s (RA) marriage. The Qur’anic guidance underscores that marriage requires not only physical maturity but also rushd—intellectual and emotional soundness—together with the free consent of the individual. By contrast, early juristic allowances for child marriage rest on weak textual bases and reflect historical socio-cultural contexts rather than binding religious directives. The paper argues that child marriage constitutes both physical and psychological harm, preventing individuals from fulfilling the moral, social, and economic responsibilities inherent in marital life. In this regard, state legislation to set a minimum age of marriage, grounded in medical and legal expertise, is not only legitimate but also consistent with the objectives of the Shari‘ah. The research concludes that Islam affirms maturity, consent, and capacity as indispensable conditions for marriage, thereby harmonizing with the principles underlying modern laws on marriage age.
Keywords: Underage, Orphan, Marriage, Maturity, Waiting Period